Hybrids in Cactaceae: current distribution and potential range of hybrids compared with parental species - Aoki-Gonçalves, Felipe; Pena, João C. [UNESP] (Taylor & Francis, 2024)
Background: Hybridisation is one of the processes that influence the evolutionary history of plants, including shifts in their distribution. It occurs unevenly across families, and the Cactaceae is an outstanding case displaying many natural hybrids. Aims: This study evaluated the current geographical distributions of hybrids within the family and compared the potential ranges of established hybrids with those of their parental species. Methods: We gathered georeferenced data of putative cactus hybrids to map their known distributions and employed ecological niche-based models (ENMs) to predict the potential ranges of established hybrids and those of their parental species. Results: While hybrids in the subfamily Cactoideae were distributed broad throughout the New World, the hybrids in the subfamily Opuntioideae were present only in North America and northern South America. ENMs showed overall resemblance between potential ranges of hybrids and parental species, except for two cases, Cylindropuntia prolifera and Selenicereus setaceus, which both had lower levels of potential range overlap and significant dissimilarities compared to parental ranges. Conclusion: Cactaceae should be considered a model for studying the evolutionary consequences of hybridisation by investigating physiological constraints of hybrids to colonise new habitats as well as the role that polyploidy has played in range shifts.
Keywords: Cactaceae; ecological niche modelling; geographic ranges; hybridisation; parental species